Improving Neutral Density Predictions Using Exospheric Temperatures Calculated on a Geodesic, Polyhedral Grid - D. R. Weimer; P. M. Mehta; W. K. Tobiska; E. Doornbos; M. G. Mlynczak; D. P. Drob; J. T. Emmert (Space Weather)
Abstract A new model of exospheric temperatures has been developed, with the objective of predicting global values with greater spatial and temporal accuracy. From these temperatures, the neutral densities in the thermosphere can be calculated, through use of the Naval Research Laboratory Mass Spectrometer and Incoherent Scatter radar Extended (NRLMSISE‐00) model. The exospheric temperature model is derived from measurements of the neutral densities on several satellites. These data were sorted into triangular cells on a geodesic grid, based on location. Prediction equations are derived for each grid cell using least error fits. Several versions of the model equations have been tested, using parameters such as the date, time, solar radiation, and nitric oxide emissions, as measured with the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on the Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite. Accuracy is improved with the addition of the total Poynting flux flowing into the polar regions, from an empirical model that uses the solar wind velocity and interplanetary magnetic field. Given such inputs, the model can produce global maps of the exospheric temperature. These maps show variations in the polar regions that are strongly modulated by the time of day, due to the daily rotation of the magnetic poles. For convenience the new model is referred to with the acronym EXTEMPLAR (EXospheric TEMperatures on a PoLyhedrAl gRid). Neutral densities computed from the EXTEMPLAR‐NRLMSISE‐00 models combined are found to produce very good results when compared with measured values.